The construction of a categorisation system for Total Care Products - Ahmed, Murshed Mohamed (2008)
Market competition and business environment of several industries is pushing companies to change their focus from hardware-based products to function based products. Total Care Products, which refer to products that are based on hardware, software and services, may be sold as a function rather than as hardware. In Total Care Products, also known as Functional Products, the supplier takes care of every aspect of the product, which allows the customer to focus on value rather than hardware. This imposes challenges that require a change in business models in which the price is related to the functionality, not to what the asset is worth. It also impacts the way business is conducted as maintenance and spare parts will no longer be sold, but instead they become a cost, which encourages the supplier to increase efficiency, decrease production cost and improve product knowledge. These factors motivated suppliers in many industries to introduce different products that have some characteristics of the Total Care concept, which made it ambiguous on how many types of Total Care products are available and what is the difference between them. In this work, a case study was conducted on the Internet industry highlighting 53 companies that come under 4 different service sectors. The main results include the establishment of a categorisation system for Total Care products that shows 4 levels and the characteristics each level possess. The categorisation system allows suppliers to classify their Total Care products in a structured way and helps their customer’s select the Total Care type that fits their requirements. The system assists suppliers to switch from conventional products to Total Care products by clarifying the different types of Total Care products they can introduce with minimum effort and business risk.